Geneva Conference (1904) in the Legal Context - Peradze, Guliko (Journal of Law, 2018)
The present article is dedicated to the First Conference of Georgian revolutionaries held in Geneva in 1904, which represents an important stage of the two decades of struggle of Georgia and its people for independence. The assembly of emigrated Georgian politicians was not paid attention by legal specialists for decades. It is possible to say that the decisions taken by political parties in this conference significantly contributed to the future tactics of national forces in the beginning of the last century. Consequently, the main task of the article is to analyse the protocols of this less known and very interesting event in legal terms and present it to the wider society. Also, it should be underlined that the study of the conference materials once again demonstrates a high level of political and legal preparation of the leadership of Georgian society at the beginning of the last century. This was well illustrated when discussing the issues such as the principles of federal arrangement of state, rights of federation subjects, quality of human rights protection in highly developed countries, knowledge of the methods to gain and protect these rights, etc.